STUDY OF THE EFFECT OF MORINGA LEAF COMBINATION (Moringa oleifera ) AND PANDAN LEAVES ( Pandanus amaryllifolius Roxb) ON THE CHEMICAL AND ORGANOLEPTIC QUALITY OF KOMBUCHA TISANE - Cannia Angelica Sitepu; Retnani Rahmiati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Moringa leaf kombucha is a functional beverage rich in nutrients and antioxidants and has various health benefits, including anti-inflammatory, antimicrobial, and anticancer properties. Kombucha from fragrant pandan leaves contains many chemical compounds including flavonoids, alkaloids, phenolics, polyphenols, and saponins and has the potential as an antibacterial and antioxidant. Kombucha from moringa leaves has a strong and pungent taste and aroma, while kombucha from fragrant pandan leaves has a sour and sweet taste and aroma. This study aims to determine the effect of the combination of moringa leaves ( Moringa oleifera ) and pandan leaves ( Pandanus amaryllifolius Roxb) on the chemical and organoleptic quality of kombucha drinks. This study used a laboratory experimental method. The experimental design used was a completely randomized design (CRD) with 1 factor, namely the different combinations of moringa leaves and pandan leaves, which consisted of 5 treatments, namely K1P1 (100:0), K2P2 (0:100), K3P3 (75:25), K4P4 (25:75), K5P5 (50:50), each repeated 3 times. The quality parameters observed included chemical (pH, total acid, and alcohol level) and organoleptic tests (color, aroma, and taste) which were assessed by 30 panelists. Data from the chemical quality research were analyzed using analysis of variance (ANOVA) and organoleptic data were tested using the nonparametric Kruskal-Wallis method. The results showed that the combination of moringa leaves and pandan leaves had a significant effect on chemical and organoleptic quality. Based on the effectiveness test, the best treatment was obtained in the K4P4 combination. (25:75) with chemical characteristics of pH 3.63, total acid 0.73%, and alcohol content 1.54%. Organoleptically, this treatment was preferred by panelists with a median score of 4 (like) for the color, taste, and aroma parameters